Discordant ROP (Retinopathy of prematurity) development in twins less than 32 weeks of gestational age - Silahli, Musa; Tekin, Mehmet; Kal, Ali; Ulusoy, Mahmut Oguz; Gokmen, Zeynel (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Retinopathy of prematurity (ROP), is a vasoprolipherative disorder of the immature retina and a major cause of preventable blindness in childhood. Although the development of ROP is multifactorial, the main reasons are lower gestational age and birth weight. However, in twins their gestational ages were the same, ROP development can be discordant. This study aims to evaluate the etiologic factors of discordant ROP development in twins. Methods: We reviewed the last 5 years’ records and found the twins whose discordant ROP development. This discordance was; 1. Different stages of ROP, 2. One sibling treated the other is not, 3. One sibling has aggressive posterior ROP the other is not, 4. one sibling has more influenced area as zones the other is not. We documented some data of these twins, as birth order, birth weight, resuscitation at birth, morbidities, the number of hemotransfusion, age of regaining birth weight, relative weight gain at 28 weeks. Results: A total of 26 cases of 13 twins were evaluated. The mean gestational age and birth weight of the whole study group were 27.7 ± 2, and 1053 ± 364 grams, respectively. We found that more transfused preterm baby in twins is more likely to show severe ROP. Additionally, sepsis and the duration of mechanical ventilation may be risk factors for more severe ROP in twins. Conclusions: We can reduce discordant retinopathy in less than 32-weeks premature twins by using methods such as cord milking and by improving non-invasive ventilation modalities.